Gordon Tullock's theory of dictatorship and revolution - Thomas Apolte (Westfälische Wilhelms-Universität Münster, Centrum für Interdisziplinäre Wirtschaftsforschung (CIW), 2015)
We assess Gordon Tullock's work on dictatorship and revolutions using a common analytic framework that captures the dynamics of mutually reinforcing perceptions within a potentially rebelling subgroup of a population. We can reconstruct all of Tullock's central findings but we also find him failing to consider revolutions as an unintended result of individual action in certain low-cost situations. That notwithstanding, one central implication of Tullock's analysis remains intact, namely that no relation can consistently be constructed between the degree of deprivation of a population on the one hand and the probability of an enforced regime change in a public uprising, at least not within the limits of methodological individualism. Hence, whoever aims at strictly inferring macro results from micro behavior must still find Tullock's work on autocracies and revolutions path-breaking.
Keywords: D02; D74; H11; 330